2021
DOI: 10.3390/genes12101580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Sex-Biased Genetic Admixture in the Americas through the Analysis of Haplotype Data

Abstract: A general imbalance in the proportion of disembarked males and females in the Americas has been documented during the Trans-Atlantic Slave Trade and the Colonial Era and, although less prominent, more recently. This imbalance may have left a signature on the genomes of modern-day populations characterised by high levels of admixture. The analysis of the uniparental systems and the evaluation of continental proportion ratio of autosomal and X chromosomes revealed a general sex imbalance towards males for Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…An additional proof of this complex scenario is the different patterns detected in the Indigenous groups currently living in Panama: Indigenous mtDNA lineages reach 100% in all Indigenous groups, while the Y-chromosome haplogroups range from 25% in the Bribri to 100% in the Naso. Similar patterns, with a modest impact of allochthonous lineages on the maternal line (<5%) and paternal lineages from external sources present in varying proportions, have been detected in Indigenous groups currently living both to the north (Costa Rica, Nicaragua, and Mexico) [21,63,65] and to the south (Colombia) [26] of Panama, as well as in other regions [67]. Within the Isthmus, we pointed out a differential post-contact impact of allochthonous Y-chromosome lineages on the Indigenous genomic pool of the western Panamanian groups that were the most homogeneous in pre-Hispanic times [36].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…An additional proof of this complex scenario is the different patterns detected in the Indigenous groups currently living in Panama: Indigenous mtDNA lineages reach 100% in all Indigenous groups, while the Y-chromosome haplogroups range from 25% in the Bribri to 100% in the Naso. Similar patterns, with a modest impact of allochthonous lineages on the maternal line (<5%) and paternal lineages from external sources present in varying proportions, have been detected in Indigenous groups currently living both to the north (Costa Rica, Nicaragua, and Mexico) [21,63,65] and to the south (Colombia) [26] of Panama, as well as in other regions [67]. Within the Isthmus, we pointed out a differential post-contact impact of allochthonous Y-chromosome lineages on the Indigenous genomic pool of the western Panamanian groups that were the most homogeneous in pre-Hispanic times [36].…”
Section: Discussionsupporting
confidence: 63%
“…Recent genomic analyses of populations currently living in the Americas confirmed the existence of sex biases in the convergence of diverse ethnic groups following European contact and colonization [ 20 , 21 , 22 ]. This sex bias was often documented by the differential inheritance of uniparental lineages with three distinct geographic/population origins: Indigenous America (IAm), Western Eurasia (WEu, including also Northern Africa), and Southern (sub-Saharan) Africa (SAf) [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2014). Given the sex bias in ancestry contribution for Latin American populations, it has been demonstrated that the X‐chromosome Native American component is higher than that of autosomes (Caputo et al., 2021; Ongaro et al., 2021). Therefore, such Native contribution to the X‐chromosome of our sample might also be responsible in part for the differences observed here.…”
Section: Discussionmentioning
confidence: 99%
“…These events, associated with wars and diseases, led to a dramatic reduction of the Indigenous people and therefore of their contribution to the present-day American gene pool. This decrease was particularly accentuated for the Y chromosome, due to the uneven male/female Native population decline and the high historical rate of male-mediated admixture into Native American communities [ 27 , 37 , 80 , 81 , 82 ]. Now, archaeogenomics fills this gap, allowing us to compare ancient with modern genomes [ 83 ], although merging all types of Y-chromosome data is complicated by the heterogeneity of markers analysed and regions investigated [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although autosomal genome-wide data allow researchers to investigate genetic admixture [ 20 , 21 ], and autosomes vs. X chromosome comparisons can assess sex-biased genetic admixture [ 22 , 23 , 24 , 25 , 26 , 27 ], only the uniparentally transmitted genetic systems, the maternally inherited mitochondrial DNA (mtDNA), and the male-specific region of Y chromosome (MSY) provide direct insights into the paternal and maternal sources of genetic ancestry. In addition, the fine-calibrated mtDNA and MSY molecular clocks [ 28 , 29 , 30 ] are key elements to date prehistoric and historical events.…”
Section: Introductionmentioning
confidence: 99%